Chaos, Care, and Critique: Performing the Contemporary Academy During the COVID-19 Pandemic - Davies, Sarah R. (Frontiers in Communication, 2021)
The starting point for this article is that the Covid-19 global pandemic has brought normally invisible, taken-for-granted aspects of contemporary societies into sharp relief. I explore the analytical affordances of this moment through a focus on the nature of the contemporary academy, asking how this was performed on ‘academic Twitter’ in the early months of the 2020 Covid-19 pandemic, and therefore contributing to work that has has characterised contemporary university and research practice and social media discussion of this. I draw on a dataset of Tweets from academic Twitter, systematically downloaded between 1 March and 24 July 2020, that are concerned with the pandemic, analysing these through a qualitative, multimodal, and practice-oriented approach. I identify themes of the disruption of academic work, of care and care practices, and of critiques of injustice and inequity within academia, but also argue that the ways in which these topics are instantiated – through distinctive repertoires of humour and of emotional honesty, positivity, and gratitude – are central to performances of academic life. The analysis thus further contributes to studies of communication to and by other publics, and in particular the ways in which the content and form of social media communication are intertwined.